Measurement accuracy: Enabling human rights for Fijian students with speech difficulties. (2nd January 2018) - Sprunt, Beth; Marella, Manjula
Abstract: Purpose : The Universal Declaration of Human Rights enshrines the rights to communication and education and measuring access to these rights for children with disabilities is fundamental. The UNICEF/Washington Group Child Functioning Module (CFM) is being promoted to measure progress against the Sustainable Development Goals for children with disabilities. This cross-sectional diagnostic accuracy study in Fiji compares parent and teacher CFM responses to the Intelligibility in Context Scale for 463 primary-aged students with and without speech difficulties. Method : Receiver operating characteristic curves were constructed to analyse CFM accuracy and determine optimal cut-off points; inter-rater reliability between teachers and parents was calculated. Result : Parent responses to the CFM speech questions achieved an area under the curve of 0.98, indicating "excellent" diagnostic accuracy. Teachers achieved 0.92 ("very good"). The Youden Index identified the optimal cut-off as "some difficulty". Conclusion : The CFM appears effective when used by parents or teachers for distinguishing between children with and without speech difficulties. While identified as the optimal cut-off statistically, the "some difficulty" category identifies too many children without speech difficulties to be simplistically applied to funding eligibility. The CFM should be used as a screening tool, followed by further assessment to confirm eligibility.